Desenvolvimento de potenciais metalofármacos de rutênio contendo 1,1’-bis(difenilfosfino)ferroceno e ligantes mercapto - Macedo, Adriana Pereira Mundim Guedes (2019)
The antimetastatic activity, high selectivity and cytotoxicity in various human tumor cell line makes ruthenium (II) complexes attractive for the development of new chemotherapeutic agents for cancer treatment. In this study, six new ruthenium complexes with biological interest ligands of general formula [Ru(NS)(bipy)(dppf)]PF6, where NS = 2-mercaptothiazoline, 2-mercapto-1-methylimidazole, 6-mercaptopyridine-3-carboxylic acid, 4,6-diamino-2-mercaptopyrimidine, 6-methyl-2-thiouracil and 2-thiouracil, were synthesized. The complexes were characterized by molar conductivity, elemental analysis, infrared and UV / visible region absorption spectroscopy, 31P{1H}, 1H and 13C{1H} nuclear magnetic resonance, cyclic and differential pulse voltammetry, and some complexes, by monocrystal X-ray diffraction. The cytotoxic activity of the complexes was evaluated against different tumor cell lines and non-tumor cells, as well as the possible mechanism of action of these complexes against MDA-MB-231 cells. In addition, the interaction of the complexes with the biomolecules of HSA and DNA, and the inhibition of the enzyme topoisomerase IB, were evaluated. The results showed high cytotoxicity and selectivity for triple-negative breast tumor cell line (MDA-MB-231), with IC50 values in the range of 0.33‒3.78 μM. The cells percentage increase in sub-G1 phase of the cell cycle analysis, distinct morphological alterations and the increase in apoptotic cells labeled with Annexin-V show that apoptosis is the mechanism of cell death induced in MDA-MB-231 cell line after treatment with the complexes. Multiple targets of action were identified for the complexes, such as induction of DNA damage, mitochondrial depolarization with reduction of mitochondrial membrane potential, increase of reactive oxygen species levels and inhibition of Topoisomerase IB enzyme. In addition, antimetastatic activities were evidenced due by both cell migration and angiogenesis in CAM membrane model inhibition. The complexes exhibited strong interaction with HSA with Kb values in the range of 105‒107 and affinity for the IA site of the protein. The complexes showed electrostatic interaction with DNA. These results observed for the synthesized complexes present promising characteristics of potential anticancer drugs.